Keamanan RESTful Web Service Menggunakan JSON Web Token (JWT) HMAC SHA-512 - Alam Rahmatulloh; Heni Sulastri; Rizal Nugroho (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
Day to day information technology is constantly evolving, allowing a wide range of technologies, programming languages, and diverse architectures to keep popping up. It makes a new problem because at present all these differences must still be able to generate an interconnected information. It needs system integration. Currently, Web Service (WS) is a solution in system integration because it can be used without looking at the platform, architecture, or programming language used by different sources. But, on WS, the existing security is still considered less. Implementation of JSON Web Token (JWT) on WS is very influential in data security. JWT is an authentication mechanism on WS, but the application of standard JWT with HMAC SHA-256 algorithm is still not optimal. Therfore, this study discussed JWT security optimization with HMAC SHA-512 algorithm, which according to some researches, this algorithm will be better than SHA-256 if compiled on 64-bit architecture. The result of this research is that the use of SHA-512 produces a better time of 1% than SHA-256, but in SHA-512 token size is 2% larger than SHA-256.